Towards an Approach to the Study of the Economic Impact of Workplace Accidents in Peru during the years 2011 to 2014: The Prevention of Occupational Risks and Productivity - Cossio Peralta, André Jorge (2016)
The Occupational Safety and Health (OSH) is an issue that has become more relevant in our country since the enforcement of Law 29783, Law SST. Notwithstanding, it has not yet reflected on how prevention measures on occupational risks could improve productivity at a company level and a national level. In this article, the author aims to demonstrate the potential costs that could lead the occupational accidents reported to the Ministry of Labor and Employment Promotion for the period between 2011-2014, from an approach to the study of the economic impact of the occupational accidents and their influence on productivity.